Evaluation of the Quality of Health Services at Turkish Palestinian Friendship Hospital in Gaza Strip, Palestine: Patients’ Perspective - Hassouna, Eman Suliman (Journal of medical and pharmaceutical sciences, 2025)
Evaluating the quality of healthcare service is very important, because it help healthcare managers to allocate resources more efficiently.  Goal: The goal of the study is to evaluate the quality of health services at Turkey Friendship Hospital in Gaza Strip, Palestine from patients' perspective.  Methodology: The study used a mixed method of quantitative and qualitative approach. The sample of the study consisted of 150 cancer patients who are admitted to the hospital during data collection period, and 10 patients for personal interviews. For data collection, the researcher used the 22-item SERVQUAL Questionnaire, and constructive interview. The researcher used SPSS version 25 for statistical analysis.  Results: The results showed that 71 (47.3%) of study participants were male patients and 79 (52.7%) were female patients, their mean age 49.58±11.691 years, mean days of admission was 3.67±1.616 days, mean years of having the disease was 3.49±2.160 years.  1.Regarding to quality of health services, the highest score was in assurance domain (m= 4.17, 83.4%), followed by tangibility (m= 4.13, 82.6%), and the lowest score was in empathy (m= 4.03, 80.6%). The overall mean score was 4.09 (81.8%).  2.Female patients expressed significant higher satisfaction with reliability (p= 0.000) and assurance (p= 0.011).  3.Patients with low education (prep school and less) expressed significant lower satisfaction with quality of health services compared to those who have secondary school and university education (p< 0.001).  4.Patients who have the disease for 2 years and less expressed significant lower satisfaction with quality of health services (p< 0.001).  5.Patients with prostatic cancer showed significant lower score in tangibility, reliability, and assurance, but no significant differences in the total score.  6.There were statistically no significant differences in patients' satisfaction with quality of health services related to age (p= 0.053), length of stay in the hospital (p= 0.340).  Conclusion: The study reflected high satisfaction with the quality of health services at Turkish Friendship Hospital. Recommendations: The study recommended the need to pay more attention to the empathy and psychological aspects of care.
Keywords: Cancer Patients; Quality of Health Services; Gaza Strip; Palestine; Turkish Friendship Hospital